Evolution of the TGF-beta superfamily with emphasis on Nodal - Shen, Yuan (2014)
Nodal is a ligand of the TGF-beta superfamily. It has the function of determining the left-right axis and inducing the endoderm and mesoderm. Nodal signals can also act as morphogens. Although it has been detected for 20 years, the relationships between different species within Nodal are still unclear. The purpose of this study is to investigate the evolution of the TGF-beta gene with the main focus on Nodal. That is: (1) to determine the relationships within the Nodal family; (2) to examine whether Nodal is duplicated or not during evolution. To achieve this, whether Nodal is monophyletic or not and the relationship of Nodal with other ligands in the TGF-beta superfamily will be examined first. The phylogenetic trees to examine the relationships among the ligands are built under software PhyML with the Maximum Likelihood method. As a result, Nodal is monophyletic, but its neighbour ligand or ligand group is nonetheless uncertain. This study demonstrates that the fish sequences are all in the group in which the bird Nodal is located. Duplication of Nodal has occurred when vertebrates evolved from Urochordata. In addition, deletions have occurred in birds and mammals.